VEGF controls microglial phagocytic response to amyloid-β - de Gea, Priscille; Benkeder, Sarah; Bouvet, Pauline; Aimard, Mélanie; Chounlamountri, Naura; Honnorat, Jérôme; Do, Le Duy; Meissirel, Claire (Frontiers in Cellular Neuroscience, 2023)
Microglial cells are well known to be implicated in the pathogenesis of Alzheimer’s disease (AD), due to the impaired clearance of amyloid-β (Aβ) protein. In AD, Aβ accumulates in the brain parenchyma as soluble oligomers and protofibrils, and its aggregation process further give rise to amyloid plaques. Compelling evidence now indicate that Aβ oligomers (Aβo) are the most toxic forms responsible for neuronal and synaptic alterations. Recently, we showed that the Vascular Endothelial Growth Factor (VEGF) counteracts Aβo-induced synaptic alterations and that a peptide derived from VEGF is able to inhibit Aβ aggregation process. Moreover, VEGF has been reported to promote microglial chemotaxis to Aβ brain deposits. We therefore investigated whether VEGF could influence microglial phagocytic response to Aβ, using in vitro and ex vivo models of amyloid accumulation. We report here that VEGF increases Aβo phagocytosis by microglial cells and further characterized the molecular basis of the VEGF effect. VEGF is able to control α-secretase activity in microglial cells, resulting in the increased cleavage of the Triggering Receptor Expressed on Myeloid cells 2 (TREM2), a major microglial Aβ receptor. Consistently, the soluble form sTREM2 also increases Aβo phagocytosis by microglial cells. Taken together, these findings propose VEGF as a new regulator of Aβ clearance and suggest its potential role in rescuing compromised microglial function in AD.